2018
DOI: 10.1186/s12906-017-2058-8
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid hesperidin exerts anti-photoaging effect by downregulating matrix metalloproteinase (MMP)-9 expression via mitogen activated protein kinase (MAPK)-dependent signaling pathways

Abstract: BackgroundHesperidin is a flavonoid with antioxidant, anti-inflammatory, and immune modulatory activities. Photoaging is a consequence of chronic exposure to the sun and ultraviolet (UV) radiation. This study was designed to evaluate the efficacy of hesperidin against photoaging of dorsal skin in hairless mice.MethodsHairless male mice (6-week-old) were divided into three groups (n = 7): control, UVB-treated vehicle, and UVB-treated hesperidin groups. UVB-irradiated mice from hesperidin group were orally admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 38 publications
2
44
0
5
Order By: Relevance
“…Matrix metalloproteinase are important during healing of wounds and their higher expression after irradiation led to delay in the healing of wounds [61,86]. Hesperidin has been reported to reduce their expression that would have also augmented the healing of irradiated wounds in the present study [87].…”
Section: Histological Studiessupporting
confidence: 51%
“…Matrix metalloproteinase are important during healing of wounds and their higher expression after irradiation led to delay in the healing of wounds [61,86]. Hesperidin has been reported to reduce their expression that would have also augmented the healing of irradiated wounds in the present study [87].…”
Section: Histological Studiessupporting
confidence: 51%
“…Hesperidin has been shown to have anticancer effects promoting apoptosis in liver cancer [6] and bladder cancer [25]. Moreover, hesperidin inhibits the expression of MMP [10] and epithelial-mesenchymal transition (EMT) related proteins, suppressing cell migration and invasion [26], as well as being an anti-inflammatory [2]. In this study, we discovered that hesperidin decreases the expression of PD-L1 in cancer cells which contributes to tumor immune evasion.…”
Section: Discussionmentioning
confidence: 91%
“…It has already been reported that hesperidin induces anticancer activity through the promotion of apoptosis [9]. A recent report showed that hesperidin also inhibits epithelial-mesenchymal transition (EMT) and the expression of members of the MMP family, and thereby inhibiting cell invasion and contributing to its anticancer activity [10]. However, the role of hesperidin in inhibiting PD-L1 mediated immune checkpoint and ultimately increasing the tumor immune response, has yet to be investigated in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It can induce a variety of biological reactions, including cell proliferation, differentiation and apoptosis. Overexpression of various oncoproteins, such as chemokines and repressor proteins, was also reported to play a pivotal role in malignant transformation of cells (45,46). MAPK/ERK and MAPK/JNK have been currently found in mammals.…”
Section: Discussionmentioning
confidence: 99%